Effects of Delayed Radical Prostatectomy and Active Surveillance on Localised Prostate Cancer-A Systematic Review and Meta-Analysis - Chan, Vinson Wai-Shun; Tan, Wei Shen; Asif, Aqua; Ng, Alexander; Gbolahan, Olayinka; Dinneen, Eoin; To, Wilson; Kadhim, Hassan; Premchand, Melissa; Burton, Oliver; Koe, Jasmine Sze-Ern; Wang, Nicole; et al. (Cancers, 2021)
External factors, such as the coronavirus disease 2019 (COVID-19), can lead to cancellations and backlogs of cancer surgeries. The effects of these delays are unclear. This study summarised the evidence surrounding expectant management, delay radical prostatectomy (RP), and neoadjuvant hormone therapy (NHT) compared to immediate RP. MEDLINE and EMBASE was searched for randomised controlled trials (RCTs) and non-randomised controlled studies pertaining to the review question. Risks of biases (RoB) were evaluated using the RoB 2.0 tool and the Newcastle-Ottawa Scale. A total of 57 studies were included. Meta-analysis of four RCTs found overall survival and cancer-specific survival were significantly worsened amongst intermediate-risk patients undergoing active monitoring, observation, or watchful waiting but not in low- and high-risk patients. Evidence from 33 observational studies comparing delayed RP and immediate RP is contradictory. However, conservative estimates of delays over 5 months, 4 months, and 30 days for low-risk, intermediate-risk, and high-risk patients, respectively, have been associated with significantly worse pathological and oncological outcomes in individual studies. In 11 RCTs, a 3-month course of NHT has been shown to improve pathological outcomes in most patients, but its effect on oncological outcomes is apparently limited.
Keywords: radical prostatectomy; treatment delay; prostate cancer; COVID-19; surgical waiting time; active surveillance